Penerapan Green Roof Dengan Integrasi Lean Construction Pada Bangunan Gedung Pelayanan Publik Kabupaten Kediri - Rahmat Heru Supriyo; Faiz Muhammad Azhari; Imam Mustofa (Jurnal Civil Engineering Study, 2025)
A This study analyzes the implementation of green roofs integrated with lean construction in the Public Service Building of Kediri Regency, focusing on construction efficiency and environmental impact. Green roofs were selected as an innovative solution to mitigate urban heat island effects, enhance rainwater absorption, and support biodiversity, while lean construction was applied to minimize material waste, time, and labor. The research methods included literature reviews, primary data collection through questionnaires (100 respondents), and data analysis using SPSS and Value Stream Mapping (VSM). The results indicate that integrating these two concepts can reduce the building's microclimate temperature by 10–15% and shorten construction time by up to 25% compared to conventional methods. Key supporting factors include the availability of local materials and policy support, while the main challenges are high initial costs and multidisciplinary coordination. The study provides recommendations for tropical climate-adapted green roof designs and lean construction strategies to improve project efficiency and reduce environmental impact, aligning with the Sustainable Development Goals (SDGs), particularly Goal 11 (Sustainable Cities) and Goal 12 (Responsible Consumption and Production).